An innovation perspective to climate change adaptation in coffee systems. Issue 97 (July 2019) - Verburg, René; Rahn, Eric; Verweij, Pita; van Kuijk, Marijke; Ghazoul, Jaboury
Abstract: Climate change is expected to have strong implications for smallholder coffee farmers and implementing adaptation measures would lessen their vulnerabilities. Adaptation measures have been identified in literature, but how these can be implemented remains unclear. Current certification programmes have the potential to provide guidance on how sustainability criteria can be addressed and taken up by farmers. We identify climate change adaptation options, their scale of application, and the necessary implementation steps. We show that implementation complexity strongly increases with the degree of climate change. With modest climatic changes, incremental adaptations might suffice, but more substantial climatic change will require radical social-institutional changes for adaptation uptake and interventions. For the majority of smallholders the implementation of any measure is largely constrained by a lack of access to knowledge networks and training material, organisational support, and (mainly financial) resources. A landscape approach that encompasses collective action and coordinated cross-sector planning can overcome some of these barriers. Certification approaches can facilitate a move in this direction. Yet, the implementation of transformative adaptations requires visioning, realignment of policies and incentives, and new market formations. This entails a repositioning and revision of certification schemes to allow for more effective adaptation uptake for the benefit of smallholders and the environment.